Foreign Investors and Control Power of Company Engaged in Energy and Basic Materials through Global Energy Crisis in Indonesia - Regina Maharani Parameswari Sapsudin; Erman Sumirat; Benny Budiawan Tjandrasa (Budapest International Research and Critics University, 2022)
This study aims to investigate the control power of foreign investors that can weaken the domestic position in managing Indonesia's natural resources when facing the global energy crisis. The control power is reflected in financial decision-making, which consists of investment decisions, funding decisions, and dividend decisions. The sample companies in this study are listed on IDX in the energy and basic materials sector in 2020, where supercycle commodities occurred. The total sample is 166 companies, with 66 companies to be observed. Using multilinear regression using ROA and Tobin's Q as control variables, the authors find the effect on investment decision making where foreign investors have a significant positive in company liability. However, its effect is negative on company equity. Foreigner investors also influence funding decisions where foreign investors have a significantly positive effect on firm size. However, foreign investors have a significantly negative effect on the decision-making of dividends.